Creating "Discovery": The Myth of Columbus, 1777–1828. (3rd May 2020) - Edney, Matthew H.
Abstract : The modern concept of "discovery" was the creation of the "second scientific revolution" in the decades to either side of 1800. The wholesale reconfiguration of knowledge practices emphasized the Romantic figure of the lone, daring adventurer who could interrogate the dynamic and ever-shifting world to discern new truths. "Discovery" was transformed from an act of investigation into an act laden with social and cultural significance, not least of Western intellectual superiority. The new conception was formulated through Anglophone reinterpretations of Columbus, within a stadial philosophy of history, as a heroic man of science, from William Robertson's History of America (1777) to Washington Irving's History of the Life and Voyages of Christopher Columbus (1828). The new concept of "discovery" further required historical assessment and validation, giving rise to the new scholarly formation of "the history of discoveries."